Extraction of Magnesium and Nickel from Nickel-Rich Serpentine with Sulfation Roasting and Water Leaching - Xiyun Yang; Lingyu Gao; Yulou Wu; Yingli Chen; Lirong Tong (Metals, 2022)
Magnesium and nickel were recovered from nickel-rich serpentine through sulfation roasting and water leaching. The factors affecting the extraction percentages of Mg and Ni were discussed. Under the conditions of the ratio of acid to ore of 0.8:1 and roasting temperature of 650 °C for 120 min, 91.6% of Mg and 88.7% of Ni but only 4.8% of Fe were extracted. The roasting kinetics of Mg and Ni were investigated. The results showed that the roasting stage was governed by internal diffusion in the temperature range of 350–650 °C, and the activation energy of nickel and magnesium were different in the time ranges of 0–30 min and 60–120 min, with 17.45 kJ⋅mol−1 (0–30 min) and 14.12 kJ⋅mol−1 (60–120 min) for magnesium and 15.48 kJ⋅mol−1 (0–30 min) and 12.46 kJ⋅mol−1 (60–120 min) for nickel. The kinetic equations were obtained.